A Comparative Study of Groundwater Vulnerability Assessment Methods - Khlif, Tagreed Hameed; Al-Aboodi, Ali H.; Ibrahim, Husham T. (Basrah Journal for Engineering Sciences, 2022)
Recently, methods have emerged to assess the vulnerability of groundwater to pollution, which has been adopted by many countries that depend on groundwater as an important and supportive resource for surface water to protect groundwater and monitor and control its pollution. Assessment methods adopt vulnerability maps and compare them with the real-life pollution map of the region. The study was conducted in Al-Teeb area, which is located in the northeast of Missan province, south of Iraq. This area is about 2450 km 2 . This study applied four models DRASTIC, GOD, SINTACS and Modified DRASTIC of vulnerability maps are analyzed using GIS technique and compared with the reality map which represent the nitrate concentration map as a basic comparison map; in order to choose the closest one with respect to the realistic acting. The results showed that 80.29 % of study area is classified under low vulnerability in DRASTIC method and moderate vulnerability in GOD, SINTACS and MD-DRASTIC which are covered 54.12 %, 83.18 % and 72.35 % of study area respectively. Pearson’s correlation coefficient was used to compare the four methods with the nitrate concentration map, where the correlation value for DRASTIC, GOD, SINTACS and MD-DRASTIC was 73.05, 49.79, 83.23 and 87.94 %, respectively. So, the MD-DRASTIC is represented the best technique for evaluating vulnerability map in the study area which can be recommended.